1999
DOI: 10.1016/s0009-9236(99)70069-x
|View full text |Cite
|
Sign up to set email alerts
|

Quinine disposition in globally malnourished children with cerebral malaria

Abstract: Severe global malnutrition and cerebral malaria have a similar effect on quinine pharmacokinetics in children. Moderate malnutrition does not potentiate cerebral malaria-mediated modifications of quinine disposition. These results suggest that current parenteral quinine regimens can be used, unmodified, to treat children with both malaria and malnutrition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(60 citation statements)
references
References 27 publications
0
58
0
2
Order By: Relevance
“…In human, Pussard and al observed that malaria and malnutrition increased plasma concentrations of quinine and reduced both the volume of distribution and the total plasma clearance [26]. Measuring the response to an acute uncomplicated Plasmodium falciparum malaria treatment with CQ, Olanrewaju WI and Johnson AW [27] observed that the proportion of children with persistence or recrudescence of parasitemia on days 4-7 and no significant reduction of parasitemia was higher among malnourished children compared to children with satisfactory nutritional status.…”
Section: Discussionmentioning
confidence: 99%
“…In human, Pussard and al observed that malaria and malnutrition increased plasma concentrations of quinine and reduced both the volume of distribution and the total plasma clearance [26]. Measuring the response to an acute uncomplicated Plasmodium falciparum malaria treatment with CQ, Olanrewaju WI and Johnson AW [27] observed that the proportion of children with persistence or recrudescence of parasitemia on days 4-7 and no significant reduction of parasitemia was higher among malnourished children compared to children with satisfactory nutritional status.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of streptomycin, children with kwashiorkor exhibited an increased Vd [48] whereas children with marasmus or underweight had a decreased Vd [48]. A decreased Vd for quinine in children with undefined PEM in one study [51] was in contrast to a separate study involving children with marasmus and marasmic-kwashiorkor where the Vd was unaffected [21]. Table 4 shows the effect of PEM on the total clearance and half-life of seven drugs that are primarily metabolised in the liver.…”
Section: Protein Binding and Distributionmentioning
confidence: 99%
“…The scaled estimate of CL for a 15-kg child (OE) was 0.37 liter/h/kg. By comparison, the mean adult CL is 0.17 liter/h/kg (Table 3), the estimated CL based on a fixed exponent of 3/4 is 0.25 liter/h/kg, and the CL from one clinical study in children (15 kg) was 0.24 liter/h/kg (118). child doses will decrease for children with higher body weights and will also decrease as the exponent approaches unity.…”
Section: Discussionmentioning
confidence: 99%